Moisture budget estimates derived from airborne observations in an Arctic atmospheric river during its dissipation - H. Dorff; H. Dorff; H. Dorff; F. Ewald; H. Konow; H. Konow; M. Mech; D. Ori; V. Schemann; A. Walbröl; M. Wendisch; F. Ament; et al. (Atmospheric Chemistry and Physics, 2025)
Atmospheric rivers (ARs) are essential for the Arctic water cycle, but observations quantifying the moisture processes of individual Arctic ARs are sparse. This study quantified the evolution of the moisture budget components of an Arctic AR derived from airborne observations from two research flights on consecutive days. We investigated how poleward transport of warm and moist air masses by ARs generates precipitation near the sea ice edge and how advection and evaporation affect the local moisture amount during the dissipation of the AR. Using observations from the High-Altitude and LOng-Range Research Aircraft (HALO), we derived the atmospheric moisture budget components (local tendency of moisture, evaporation, moisture transport divergence, and precipitation) within an Arctic AR during the HALO-(𝒜𝒞)3 aircraft campaign. The budget components were quantified in sectors ahead of the AR-embedded cold front using airborne observations from dropsondes, radiometers, and a radar device and compared with values derived from reanalyses and numerical weather prediction simulations.